2008
DOI: 10.1302/0301-620x.90b8.20189
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hand-held ultrasound scanning in detecting meniscal tears

Abstract: The diagnosis of a meniscal tear may require MRI, which is costly. Ultrasonography has been used to image the meniscus, but there are no reliable data on its accuracy. We performed a prospective study investigating the sensitivity and specificity of ultrasonography in comparison with MRI; the final outcome was determined at arthroscopy. The study included 35 patients with a mean age of 47 years (14 to 73). There was a sensitivity of 86.4% (95% confidence interval (CI) 75 to 97.7), a specificity of 69.2% (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
0
25
1
Order By: Relevance
“…[4][5][6][7][8][9] Reported sensitivities for ultrasonographic diagnosis of meniscal tears range from 83.3 to 100% and reported specificities range from 69.2 to 95%. [4][5][6][7][8][9] Differences in sensitivity and specificity among studies likely stem from variations in patient population, ultrasonographer's technique and level of expertise, and the reference standard used. In the study by Cook et al comparing ultrasonography and MRI for diagnosis of meniscal pathology in patients with acute knee pain, they reported a sensitivity of 91.2% and specificity of 84.2% for ultrasonography compared with a sensitivity of 91.7% and specificity of 66.7% for MRI using arthroscopic diagnosis as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Reported sensitivities for ultrasonographic diagnosis of meniscal tears range from 83.3 to 100% and reported specificities range from 69.2 to 95%. [4][5][6][7][8][9] Differences in sensitivity and specificity among studies likely stem from variations in patient population, ultrasonographer's technique and level of expertise, and the reference standard used. In the study by Cook et al comparing ultrasonography and MRI for diagnosis of meniscal pathology in patients with acute knee pain, they reported a sensitivity of 91.2% and specificity of 84.2% for ultrasonography compared with a sensitivity of 91.7% and specificity of 66.7% for MRI using arthroscopic diagnosis as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound scanning has been shown to have comparable accuracy as conventional MRI in the diagnosis of meniscal tears in adults [10]. Its use for diagnosing meniscal tears in children is not clear, but the vascularity of the immature meniscus would not be expected to produce artifact resembling a tear.…”
Section: Discussionmentioning
confidence: 99%
“…20 Fuchs and Chylarecki 21 found that using two indirect ultrasonography findings in combination (echo-poor space at the femoral insertion of the ACL and protrusion of the posterior fibrous capsule) increased the predictive value to 98% for the detection of acute ACL ruptures. In diagnosing meniscus tears, Shetty et al 22 found that ultrasonography had a sensitivity of 86.4% and a specificity of 69.2%, compared with a sensitivity of 86.4% and a specificity of 100% with MRI. Similarly, Akatsu et al 23 found a sensitivity of 88% and a specificity of 85% for ultrasonography in diagnosing meniscus tears.…”
Section: Knee Pathologymentioning
confidence: 99%